PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIKA PENYAJIAN DATA DALAM TABEL SISWA KELAS III SEKOLAH DASAR - Uci Ana; Dini Rahmadani; Rapita Aprilia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low mathematical critical thinking ability of third-grade students at SD Negeri 10 Langsa on the material of presenting data in tables. Students experienced difficulties in interpreting data, analyzing information, providing logical reasons, and drawing conclusions. The purpose of this research was to determine the effect of the Problem Based Learning (PBL) learning model on the mathematical critical thinking ability of third-grade students at SD Negeri 10 Langsa on the material of presenting data in tables. This research used a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The research sample consisted of 37 students, comprising 17 students from class III A as the experimental class and 20 students from class III B as the control class. The research instrument was a mathematical critical thinking essay test that had been declared valid and reliable. Data analysis was conducted through normality tests, homogeneity tests, and hypothesis testing using the Independent Samples t-test assisted by IBM SPSS Statistics version 25. The results showed that the average posttest score of the experimental class was 83.97, which was higher than the control class average of 65.50. Based on the Independent Samples t-test results, the t-count value was 9.030, while the t-table value at a 5% significance level (α = 0.05) with degrees of freedom (df) of 35 was 2.030. Because the t-count > t-table (9.030 > 2.030), H₀ was rejected and Hₐ was accepted. This result was supported by the Sig. (2-tailed) value of 0.000, which is less than 0.05 (0.000 < 0.05). Therefore, it can be concluded that the Problem Based Learning (PBL) learning model has a significant effect on the mathematical critical thinking ability of third-grade students at SD Negeri 10 Langsa on the material of presenting data in tables. Thus, the PBL model can be used as an alternative learning model to improve students' critical thinking abilities in elementary school mathematics learning.